counterweight
Patent Information
- Application Number
- CN202480087393.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2026-11-03
AI Technical Summary
此外,在制备平衡配重用组合物时,由于其为膏状的高粘度,因此不得不通过手工作业来进行双液的混合及涂布,从而难以实现自动化,作业性较差
[0017]根据本发明,可提供一种使用常温下为固体的湿气固化型粘接剂的平衡配重用组合物及由该平衡配重用组合物而得的平衡配重。
Smart Images

Figure SMS_4 
Figure SMS_22 
Figure SMS_46
Abstract
Description
Technical Field
[0001] This invention relates to compositions for balancing weights and balancing weights. Background Technology
[0002] Generally, there are two methods for adjusting the equilibrium state of a rotating body based on dynamic balance. The first method is to remove locally unbalanced parts and achieve overall equilibrium. The second method is to apply balancing weights to locally unbalanced parts to achieve overall equilibrium. Compared to the first method, the second method is simpler and more cost-effective.
[0003] To correct unbalanced rotation caused by non-uniform moments of inertia, a common method is to apply balancing weights around the circumference of the rotating body to correct the imbalance.
[0004] As a balancing weight composition, for example, a balancing weight composition comprising an adhesive made of epoxy resin is used. As such a balancing weight composition, for example, the epoxy resin composition "Dreamweight" for balance adjustment manufactured by Toa Densei Corporation is well known.
[0005] Previously, the attachment position of the counterweight (balance weight) relative to the rotating body was determined in advance, and the epoxy resin composition of the balance weight was attached to that part. The balance of the rotating body was adjusted by curing at room temperature and / or by heating.
[0006] Patent documents 1-3 disclose balancing weights for correcting unbalanced rotation of rotating bodies. These balancing weight compositions are primarily two-component mixtures obtained by mixing a main agent and a curing agent and allowing them to react and cure. However, the time from mixing the main agent and curing agent to the point of use (usable time) is limited; the balancing weight composition must be applied to the object within this usable time. Furthermore, due to its high viscosity as a paste, the preparation of the balancing weight composition necessitates manual mixing and application, making automation difficult and resulting in poor workability.
[0007] Patent documents 4 and 5 disclose a composition for balancing and counterweighting, which contains metal powder with tungsten as the main component and a viscosity of 1 Pa at room temperature. s~50Pa This is a single-component curing adhesive with thixotropic properties. The balanced weight composition is considered easy to manage or handle, has excellent workability, and is further facilitated by automated coating.
[0008] Patent documents Patent Document 1: Japanese Patent Application Publication No. 2001-298929 Patent Document 2: Japanese Patent Application Publication No. 2001-298925 Patent Document 3: Japanese Patent Application Publication No. 3-107646 Patent Document 4: Japanese Patent Application Publication No. 2004-36675 Patent Document 5: Japanese Patent Application Publication No. 2005-121166 Summary of the Invention Traditional counterweight compositions are difficult to automate in terms of preparation, coating, and formulation, resulting in poor workability. Furthermore, when using adhesives that are liquid at room temperature, if the equilibrium state is measured immediately after coating or formulation, there is a risk of sagging or displacement from the coating or formulation position because the counterweight composition has not yet cured. The next step can only be performed after curing, further complicating workability.
[0009] The problem that this invention aims to solve is: (1) A composition for balancing weights using a moisture-curing adhesive that is solid at room temperature, and a balancing weight obtained from the composition; and / or, (2) A balancing weight composition and a balancing weight obtained from the composition are provided. The balancing weight composition is easy to automate during preparation, coating, and preparation. It has a fast curing speed, excellent fast curing and fast adhesion. Even if the equilibrium state is measured immediately after coating and preparing the balancing weight composition, the occurrence of sagging or displacement can be suppressed, and the next process can be carried out. It has excellent workability.
[0010] The inventors conducted in-depth research to solve the above-mentioned problems and found that the above-mentioned problems could be solved by using a balancing weight with a specific structure, thus completing the present invention.
[0011] Specifically, it is shown below.
[0012] Item 1: A composition for balancing weights, characterized in that it comprises: Moisture-curing adhesive that is solid at room temperature (A); Tungsten powder (B) The composition for balancing counterweights is a solid at room temperature and has a specific gravity of 8.5 or less.
[0013] Item 2: The composition for balancing weights according to Item 1, characterized in that the moisture-curing adhesive (A), which is solid at room temperature, is mainly composed of a urethane prepolymer containing isocyanate groups or a polymer containing crosslinked silicone groups.
[0014] Item 3: The composition for balancing weights according to Item 1 or 2, characterized in that the moisture-curing adhesive (A), which is solid at room temperature, has a viscosity of 50 Pa at 120°C. Below s, The particle size of the tungsten powder (B) is in the range of 0.1~200μm.
[0015] Item 4: A counterweight, characterized in that it is made by applying the counterweight composition described in any one of items 1 to 3 to a desired part of a rotating body to adjust the balance of the rotating body.
[0016] Item 5: A method characterized in that it is a method of applying the balancing weight composition described in any one of items 1 to 3 to the application site of a rotating body to adjust the balance.
[0017] According to the present invention, a balancing weight composition using a moisture-curing adhesive that is solid at room temperature and a balancing weight obtained from the balancing weight composition can be provided.
[0018] Furthermore, according to the present invention, a balancing weight composition and a balancing weight obtained from the composition can be provided. The balancing weight composition is easy to automate during preparation, coating, or preparation. It has a fast curing speed and excellent fast curing and fast adhesion. Even if the equilibrium state is measured immediately after coating or preparing the balancing weight composition, the occurrence of sagging or displacement can be suppressed, allowing the next process to proceed. It has excellent workability. Detailed Implementation
[0019] The balancing composition of the present invention comprises a moisture-curing adhesive (A) that is solid at room temperature and tungsten powder (B), which is solid at room temperature and has a specific gravity of 8.5 or less.
[0020] The balancing weight of the present invention is applied to the desired part of the rotating body by means of the balancing weight composition to adjust the balance of the rotating body.
[0021] The inventors have discovered that the equilibrium weight comprising a moisture-curing adhesive (A) that is solid at room temperature and tungsten powder (B) that is solid at room temperature has the following characteristics: (i) If the counterweight is heated and melted during use, it can be easily coated onto the rotating body; (ii) Since the moisture-curing adhesive cures rapidly after application, the overall balance (equilibrium state) of the rotating body can be quickly confirmed. (iii) The moisture in the air can be used to cross-link the moisture-curing adhesive, thereby significantly improving the adhesion to the rotating body.
[0022] The following is a detailed explanation.
[0023] [Definitions and meanings of the terms] The definitions and meanings of the terms used in this manual are as follows.
[0024] "Room temperature" or "room temperature" is 23°C.
[0025] "Moisture-curing adhesives that are solid at room temperature" refers to moisture-curing adhesives that are crystalline, partially crystalline, or glassy amorphous, and whose softening point or melting point obtained by the ring and ball method exceeds 23°C.
[0026] "Melting point" refers, for example, to the maximum value of a curve obtained by dynamic differential calorimetry (differential scanning calorimetry: DSC) during heating operation, and is the temperature at which a solid state changes into a liquid state.
[0027] "Moisture-curing adhesives" refer to adhesives that cure through a chemical reaction with water or water vapor.
[0028] [Composition for balancing weights] <Moisture-curing adhesive that is solid at room temperature (A)> The "moisture-curing adhesive (A) which is solid at room temperature" and is a component of the balancing composition of the present invention is a solid at room temperature (23°C) and standard atmospheric pressure (1013.25 hPa) (with a softening point or melting point exceeding 23°C obtained by the ring and ball method), and is an adhesive that is cured by chemical reaction with water or water vapor.
[0029] As "a moisture-curing adhesive that is solid at room temperature (A)", an adhesive such as "reactive hot melt adhesive" or "single-component moisture-curing reactive hot melt adhesive" can be used.
[0030] Examples of moisture-curing adhesives (A) that are solid at room temperature include adhesives with isocyanate-containing urethane prepolymers Aa as the main component and adhesives with crosslinked silicone polymers Ab as the main component.
[0031] (Aa, a urethane prepolymer containing isocyanate groups) The manufacturing method of the urethane prepolymer Aa containing isocyanate groups is not particularly limited as long as it is a prepolymer with isocyanate groups. For example, it can be obtained by reacting a polyisocyanate component with a polyol component in a manner where the polyisocyanate component is in excess. For example, the molar ratio of isocyanate groups in the polyisocyanate component to hydroxyl groups in the polyol component, i.e., isocyanate group / hydroxyl group, is greater than 1.0, preferably 1.2 or more, more preferably 1.3 or more, further preferably 1.4 or more, for example, 2.5 or less, preferably 2.3 or less, more preferably 2.1 or less. For good coatability, the isocyanate group / hydroxyl group ratio is preferably 1.2 or more, and for good curability, it is preferably 2.5 or less.
[0032] {Polyisocyanate components} There are no particular limitations on the polyisocyanate component as long as it is a compound having at least two isocyanate groups in one molecule. For example, one or more of the following can be listed: aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic aliphatic polyisocyanates, aromatic polyisocyanates, and derivatives of these polyisocyanates.
[0033] Examples of aliphatic polyisocyanates include substances having aliphatic hydrocarbon groups having 1 to 20 carbon atoms. Examples include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylidene diisocyanate, 1,2-butylidene diisocyanate, 2,3-butylidene diisocyanate, 1,3-butylidene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, methyl 2,6-diisocyanate hexanoate, and lysine diisocyanate (2-isocyanate). Aliphatic diisocyanates such as ethyl 2,6-diisocyanate hexanoate; aliphatic triisocyanates such as 1,6-diisocyanate-3-methylhexane, 1,4,8-triisocyanate octane, 1,6,11-triisocyanate undecane, 1,8-diisocyanate-4-methyl octane, 1,3,6-triisocyanate hexane, and 2,5,7-trimethyl-1,8-diisocyanate-5-methyl octane; and more than one of the following.
[0034] Examples of alicyclic polyisocyanates include substances having alicyclic hydrocarbon groups having 3 to 20 carbon atoms. Examples of alicyclic diisocyanates include 1,3-cyclopentane diisocyanate, 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, isophorone diisocyanate, 4-methyl-1,3-cyclohexene diisocyanate (hydrogenated TDI), 2-methyl-1,3-cyclohexene diisocyanate, 1,3- or 1,4-bis(isocyanomethyl)cyclohexane or mixtures thereof (hydrogenated phenyl diisocyanate), dicyclohexylmethane diisocyanate (hydrogenated MDI), norbornene diisocyanate, etc.; 1,3,5-triisocyanocyclohexane, 1,3,5-trimethylisocyanocyclohexane, 2-(3-isocyanopropyl)-2,5-bis(isocyanomethyl)-bicyclo(2.2.1)heptane, 2-(3-isocyanopropyl)-2,5-bis(isocyanomethyl)-bicyclo(2.2.1)heptane, etc. 3-(3-isocyanopropyl)-2,5-di(isocyanomethyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanoethyl)-2-isocyanomethyl-3-(3-isocyanopropyl)-bicyclo(2.2.1)heptane, 6-(2-isocyanoethyl)-2-isocyanomethyl One or more of the following alicyclic triisocyanates: -3-(3-isocyanopropyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanoethyl)-2-isocyanomethyl-2-(3-isocyanopropyl)-bicyclo(2.2.1)heptane, 6-(2-isocyanoethyl)-2-isocyanomethyl-2-(3-isocyanopropyl)-bicyclo(2.2.1)heptane, etc.
[0035] Examples of aromatic aliphatic polyisocyanates include, for example, one or more aromatic aliphatic diisocyanates selected from 1,3- or 1,4-phenylenedimethyl diisocyanate or mixtures thereof (XDI), ω,ω'-diisocyano-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyano-1-methylethyl)benzene (tetramethylphenyldimethyl diisocyanate) or mixtures thereof; aromatic aliphatic triisocyanates such as 1,3,5-triisocyanomethylbenzene; etc.
[0036] Examples of aromatic polyisocyanates include, for example, those selected from meta- or para-phenylene diisocyanate, diphenylmethane diisocyanate (MDI), 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), mixtures of 2,4-TDI and 2,6-TDI, 4,4'-toluidine diisocyanate, 4,4'- Aromatic diisocyanates such as diphenyl ether diisocyanate; aromatic triisocyanates such as triphenylmethane-4,4',4''-triisocyanate, 1,3,5-triisocyanobenzene, and 2,4,6-triisocyanotoluene; aromatic tetraisocyanates such as 4,4'-diphenylmethane-2,2',5,5'-tetraisocyanate; aromatic polyisocyanates such as polymethylene polyphenyl polyisocyanate (crude MDI, polymeric MDI); and more than one of the following:
[0037] As derivatives of polyisocyanates, examples include dimers, trimers, biuret, urethane, urea diketone, urea imine, isocyanurate, oxadiazine trione, etc.
[0038] Of these, one or more are preferably selected from phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, phenylene diisocyanate, and tetramethylphenyl diisocyanate. From the perspective of preparing a hot melt adhesive for use by heating and melting, diphenylmethane diisocyanate with a low vapor pressure upon heating is particularly preferred.
[0039] {Polyols} There are no particular limitations on polyol components, as long as each molecule contains at least two hydroxyl groups. Polyol components can be either low molecular weight polyols or high molecular weight polyols (polymer polyols).
[0040] To obtain the isocyanate-containing urethane prepolymer Aa constituting the room-temperature solid moisture-curing adhesive involved in this invention, it is preferable to include at least one polyester polyol having at least two hydroxyl groups in its polyol composition and being solid at room temperature, particularly a polyester polyol that is at least partially crystalline. This allows the moisture-curing adhesive to cure rapidly after coating, thereby enabling rapid confirmation of the overall balance (equilibrium state) of the rotating body.
[0041] In this invention, acrylic polyols and / or polycarbonate polyols that are solid at room temperature may be used as polyol components. Furthermore, to improve coatability or flexibility after moisture curing, one or more of polyether polyols, polyester polyols, polyolefin polyols, castor oil polyols, etc., that are liquid at room temperature, may be used as polyol components.
[0042] - Polyester polyols that are solid at room temperature- Polyester polyols that are solid at room temperature are polyols with two or more hydroxyl groups and polyester repeating units in one molecule.
[0043] Polyester polyols can be obtained, for example, by reacting a polyol component having two or more hydroxyl groups with a polycarboxylic acid component having two or more carboxyl groups or their reactive derivatives under conditions of excess polyol component. Alternatively, polyester polyols can be obtained by linking them with diisocyanates. Furthermore, they can be prepared by ring-opening polymerization of cyclic polyesters such as polycaprolactone derivatives using bifunctional initiator molecules such as 1,6-hexanediol.
[0044] As a polyol component having two or more, preferably two or three, more preferably two hydroxyl groups, examples include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, neopentanediol, 1,3-butanediol, 2,2-diethyl-1,3-propanediol, 2,2-diethylpropanediol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butyl- The following are one or more of the following: aliphatic diols having 2 to 16 carbon atoms, such as 1,3-propanediol, 2-methyl-1,8-octanediol, and 2,4-diethyl-1,5-pentanediol; aliphatic diols having ether bonds, such as diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol; aromatic diols obtained by ring-opening addition reactions of bisphenol compounds such as bisphenol A and bisphenol F with ethylene oxide, propylene oxide, γ-butyrolactone, or ε-caprolactone; and aliphatic triols such as trimethylolpropane, trimethylolpropane, pentaerythritol, and glycerol. Among these, from the perspective of improving the crystallinity of the obtained polyester polyol, one or more linear aliphatic diols having 2 to 14 carbon atoms are preferred, and more preferably 2 to 12 carbon atoms.
[0045] As a polycarboxylic acid component having two or more carboxyl groups or their reactive derivatives, examples include linear aliphatic dicarboxylic acids with 2 to 16 carbon atoms, such as oxalic acid, malonic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, and 1,12-dodecanedicarboxylic acid; aromatic dicarboxylic acids with 8 or more carbon atoms, such as terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, and biphenyl dicarboxylic acid; and their reactive derivatives (acid halides, acid anhydrides, acid esters, etc.). Among these, from the perspective of improving the crystallinity of the obtained polyester polyol, it is preferable to select one or more linear aliphatic dicarboxylic acids or their reactive derivatives with 6 to 14 carbon atoms, preferably 8 to 12.
[0046] {Acrylic polyols that are solid at room temperature} Examples of acrylic polyols that are solid at room temperature include (meth)acrylic polymers having hydroxyl groups, or compounds with hydroxyl groups introduced at the end of acrylic polymers.
[0047] By incorporating acrylic polyols, the curing time of the composition for balancing weights can be adjusted or the cured product after moisture curing can be given high toughness.
[0048] {Polycarbonate polyols that are solid at room temperature} As a polycarbonate polyol that is solid at room temperature, for example, a polycarbonate polyol obtained by reacting carbonate and / or carbonyl chloride with a diol can be used. This can improve the hydrolysis resistance and moisture adhesion of the cured composition for balancing and weighting.
[0049] As carbonates, one or more can be selected from dimethyl carbonate, diphenyl carbonate, etc.
[0050] As a diol, examples include straight-chain aliphatic diols such as 1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol; branched-chain aliphatic diols such as neopentanediol, 3-methyl-1,5-pentanediol, and 2-methyl-1,8-octanediol; alicyclic diols such as 1,4-cyclohexanediol; and aromatic diols such as bisphenol A; and more than one of the following.
[0051] Here, polycarbonate polyols containing only one type of straight-chain aliphatic diol are solid at room temperature and exhibit crystallinity. In this invention, polycarbonate polyols containing only 1,6-hexanediol are preferably used.
[0052] {Polyols that are liquid at room temperature} In this invention, the polyol component may also include, as needed, a polyol that is liquid at room temperature. Examples of polyols that are liquid at room temperature include, for example, one or more selected from polyether polyols, aromatic polyester polyols, polycarbonate polyols, etc.
[0053] -Polyether polyol- Polyether polyols that are liquid at room temperature may be selected from one or more of the following: polypropylene glycol (PPG), polyethylene glycol (PEG), and polytetramethylene glycol (PTMG).
[0054] The number average molecular weight of the polyether polyol is not particularly limited. For example, it is 500 or more, preferably 1,000 or more, more preferably 2,000 or more, for example, 30,000 or less, preferably 20,000 or less, more preferably 15,000 or less.
[0055] Diol is preferred as the polyether polyol.
[0056] Furthermore, compounds obtained by copolymerizing two or more polyether polyols can also be used as polyether polyols. For example, polyoxyethylene-oxypropylene block copolymer diols are shown. The terminal group of this diol is a primary hydroxyl group, which reacts well with isocyanate groups, and is therefore preferred. In the polyoxyethylene-oxypropylene block copolymer diol, the ethylene oxide content is preferably 5% by weight or more, more preferably 90% by weight or less, more preferably 40% by weight or less, and even more preferably 20% by weight or less.
[0057] -Polyester polyols- As a polyester polyol that is liquid at room temperature, one or more can be selected from aromatic polyester polyols, alicyclic polyester polyols, aliphatic polyester polyols, etc. For example, by mixing aromatic polyester polyols that are liquid at room temperature, a moisture-curing adhesive with excellent bonding strength that is solid at room temperature can be prepared.
[0058] For example, an aromatic polyester polyol having a number average molecular weight of 2,000 to 5,000 and a glass transition temperature of 30°C or higher, and an aromatic polyester polyol having a number average molecular weight of 400 to 3,500 and a glass transition temperature of 20°C or lower, may be used.
[0059] There is no particular limitation on the glass transition temperature (Tg) of the polyester polyol. From the perspective of further improving adhesion, it is preferably below 20°C, and more preferably above -30°C.
[0060] -Polycarbonate polyols- As polycarbonate polyols that are liquid at room temperature, examples of copolycarbonate diols in terms of diol composition include those composed of 3-methyl-1,5-pentanediol and 1,6-hexanediol, those composed of 1,5-pentanediol and 1,6-hexanediol, and those composed of 2-methyl-1,8-octanediol and 1,9-nonanediol. By using the above-mentioned polycarbonate polyols that are liquid at room temperature, the flexibility of the cured film of the moisture-curing adhesive that is solid at room temperature according to the present invention can be improved.
[0061] The number average molecular weight of the polycarbonate polyol is preferably 500 or more, more preferably 1,000 or more, more preferably 5,000 or less, and more preferably 4,000 or less, from the perspective of further improving the adhesiveness of the moisture-curing adhesive that is solid at room temperature according to the present invention.
[0062] There is no particular limitation on the glass transition temperature (Tg) of the polycarbonate polyol. From the perspective of further improving adhesion, it is preferably below 20°C, and more preferably above -30°C.
[0063] (Polymers Ab containing cross-linked silicone groups) The crosslinked silicon-containing polymer Ab of this invention is not particularly limited to any polymer containing a crosslinked silicon group in its molecule. For example, it can be obtained by reacting the isocyanate group of an isocyanate-containing urethane prepolymer Aa with a compound having a functional group that reacts with the isocyanate group and a crosslinked silicon group. Alternatively, it can be obtained by reacting a polymer or compound having a functional group that reacts with the isocyanate group with a polymer or compound having both an isocyanate group and a crosslinked silicon group. Here, the functional group that reacts with the isocyanate group is a group containing active hydrogen, such as a hydroxyl, amino, or mercapto group, and the crosslinked silicon group is an alkoxysilyl group, a silanol group, or the like.
[0064] Examples of compounds having functional groups that react with isocyanate groups and crosslinking silicon groups include silane coupling agents having functional groups such as amino, hydroxyl, and mercapto groups that react with isocyanate groups.
[0065] As a silane coupling agent having a functional group that reacts with an isocyanate group, examples include, for example, mercaptosilanes such as γ-mercaptopropyltrimethoxysilane; hydroxyl-containing silanes such as 2-ethoxy-4(5)-(2-triethoxysilylethyl)cyclohexane-1-ol; primary aminosilanes such as 3-aminopropyltrimethoxysilane; secondary aminosilanes such as N-butyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltrimethoxysilane; Michael adducts of primary aminosilanes such as dimethyl and diethyl N-(3-trimethoxysilylpropyl)aminosuccinate; analogs of the above-mentioned aminosilanes having an alkoxy group with 1 to 6 carbon atoms, such as ethoxy or isopropoxy, instead of the methoxy group bonded to the silyl group; and one or more of the following.
[0066] In this invention, secondary aminosilanes are preferred. This is because they react more gently with isocyanate groups compared to primary aminosilanes, thereby making it easier to obtain the target compound.
[0067] The crosslinked silicon-containing polymer Ab of the present invention, in addition to the polymers described above, may include, for example, one or more of the following: a crosslinked silicon-containing (meth)acrylic polymer obtained by reacting a polymer or compound having isocyanate groups with a (meth)acrylic polymer having functional groups that react with isocyanate groups and crosslinked silicon groups; or a crosslinked silicon-containing (meth)acrylic polymer obtained by reacting a polymer or compound having isocyanate groups and crosslinked silicon groups with a (meth)acrylic polymer having functional groups that react with isocyanate groups, etc. Here, the functional group that reacts with the isocyanate group is a group containing active hydrogen such as hydroxyl, amino, or mercapto, and the crosslinked silicon group is an alkoxysilyl group, silanol group, etc.
[0068] As (meth)acrylic acid polymers having functional groups that react with isocyanate groups and crosslinkable silicone groups, (meth)acrylic acid copolymers obtained by polymerizing monomer components containing monomers having functional groups that react with isocyanate groups, such as hydroxyl groups, can be used. Crosslinkable silicone-containing (meth)acrylic acid polymers that are solid at room temperature (23°C) and have hydroxyl groups at the ends are particularly preferred. They have a "(hard segment)-(soft segment)-(hard segment)" type block polymer structure composed of "hard segments" such as (meth)acrylic acid methyl acrylate copolymers that are solid at room temperature and "soft segments" such as polyethers or crystalline polyesters, thus improving toughness. Furthermore, by containing crosslinkable silicone groups such as alkoxysilyl groups, a crosslinking reaction can be carried out, thereby further improving adhesion or heat resistance.
[0069] The cross-linked silicone-containing (meth)acrylic polymer is preferably a substance having one hydroxyl group. By using a cross-linked silicone-containing (meth)acrylic polymer having only one hydroxyl group, the gelation of moisture-curing adhesives that are solid at room temperature can be suppressed. Here, the method of introducing the hydroxyl group into the cross-linked silicone-containing (meth)acrylic polymer is not particularly limited. For example, the following methods can be listed. In addition, the hydroxyl group can also be introduced beyond the terminal.
[0070] (1) Copolymerize unsaturated compounds with hydroxyl groups.
[0071] (2) Polymerization is carried out using an initiator or chain transfer agent with hydroxyl groups.
[0072] (3) Reactions using thiols with hydroxyl groups or polymerization using thiols with hydroxyl groups and metallocene compounds.
[0073] In addition, the method in (3) can be the method described in Japanese Patent No. 5222467.
[0074] As a method for introducing a hydroxyl group, from the perspective of being able to introduce one hydroxyl group, polymerization methods using thiols containing hydroxyl groups and metallocene compounds are preferred. Examples of thiols containing hydroxyl groups include 2-mercaptoethanol.
[0075] The number-average molecular weight of the crosslinked silicone-based (meth)acrylic polymer is not particularly limited. For example, it is 1,000 or more, preferably 2,000 or more, more preferably 3,000 or more, for example, 50,000 or less, preferably 30,000 or less, more preferably 15,000 or less.
[0076] As a constituent monomer of crosslinked silicone-based (meth)acrylate polymers, that is, monomers having functional groups such as hydroxyl groups that react with isocyanate groups, alkyl (meth)acrylates with hydroxyl groups are preferred. Examples of such compounds include monohydroxy acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl acrylate; and polyhydroxy acrylates such as glycerol mono(meth)acrylate. Among these, monohydroxy acrylates such as 2-hydroxyethyl (meth)acrylate are preferred. Furthermore, the amount of alkyl (meth)acrylate with hydroxyl groups used per molecule of the crosslinked silicone-based (meth)acrylate polymer is preferably an amount with an average of 0.5 to 3 hydroxyl groups, more preferably an amount with an average of 1.1 to 2 hydroxyl groups.
[0077] In this invention, when preparing a polymer Ab containing crosslinked silicon groups, the number of silane groups in the polymer Ab containing crosslinked silicon groups can be adjusted (reduced) by using a compound having a functional group that reacts with an isocyanate group but does not have crosslinked silicon groups. This allows adjustment of the crosslinking density of the cured polymer Ab containing crosslinked silicon groups, resulting in adjustments to the softness and / or stretchability of the cured film. Here, examples of functional groups that react with isocyanate groups include hydroxyl, amino, and mercapto groups; hydroxyl and amino groups are preferred, and secondary amino groups are more preferred from the perspective of stably manufacturing a moisture-curing adhesive that is solid at room temperature.
[0078] As a compound having one functional group that reacts with an isocyanate group and not having a crosslinking silane group, examples include one or more monoalkyl alcohols selected from straight-chain or branched monoalkyl alcohols such as 2-ethylhexanol, lauryl alcohol, stearyl alcohol, and behenyl alcohol; ether alcohols or ester alcohols such as propylene glycol monoacetate, diethylene glycol monoacetate, and polyoxypropylene monohydric alcohol; monoamines such as octylamine, dodecylamine, hexadecylamine, stearylamine, and behenylamine; and monoamines such as dibutylamine, butyloctylamine, dioctylamine, distearate, and butylstearylamine.
[0079] From the perspective of curability, the average number of crosslinked silicon groups in each molecule of the polymer Ab containing crosslinked silicon groups is preferably 1.0 or more, more preferably 1.2 or more, even more preferably 1.4 or more, and particularly preferably 1.6 or more. From the perspective of physical properties, the average number is preferably 4.0 or less, more preferably 3.0 or less, even more preferably 2.5 or less, and particularly preferably 2.0 or less.
[0080] The cross-linked silicone-based polymer Ab of this invention can also be a moisture-curing (meth)acrylic compound that is solid at room temperature. For example, a cross-linked silicone-based (meth)acrylic polymer is preferred.
[0081] The glass transition temperature of (meth)acrylic polymers containing crosslinked silicone groups is, for example, above -20°C, preferably above -10°C, for example, below 120°C, and more preferably below 100°C.
[0082] The crosslinking silicon group of (meth)acrylic polymers containing crosslinking silicon groups is, for example, a group having a crosslinking group such as an alkoxy group bonded to a silicon atom and capable of crosslinking through a silanol condensation reaction. Examples of crosslinking silicon groups are those represented by the following general formula (I).
[0083] [Chemistry 1]
[0084] In general formula (I), R 11R represents alkyl groups with 1 to 20 carbon atoms, substituted alkyl groups with 1 to 20 carbon atoms, cycloalkyl groups with 3 to 20 carbon atoms, aryl groups with 6 to 20 carbon atoms, and aralkyl groups with 7 to 20 carbon atoms. 11 When two or more are present, they can be the same or different. X represents alkoxy groups, and when two or more X are present, they can be the same or different. a represents 0, 1, 2, or 3. In the crosslinked silicone group of general formula (I), it is preferable that a is 2 or 3. When a is 3, the curing speed is greater than when a is 2. In the case of the crosslinked silicone group represented by general formula (I), considering curability, it is preferable that a is 2 or more.
[0085] As R 11 Specific examples include alkyl groups such as methyl and ethyl, substituted alkyl groups such as methoxymethyl, and cycloalkyl groups such as cyclohexyl. Among these, methyl is preferred.
[0086] There is no particular limitation on the alkoxy group represented by X, as long as it is a conventionally known alkoxy group. Among alkoxy groups, the group with fewer carbon atoms has higher reactivity, as shown in the order of methoxy > ethoxy > propoxy; the more carbon atoms, the lower the reactivity. Although the choice can be made according to the purpose or application, methoxy or ethoxy is usually used.
[0087] Specifically, from the perspective of high reactivity, the crosslinking silicone group is preferably alkoxysilyl, such as trimethoxysilyl or triethoxysilyl, and more preferably trimethoxysilyl. When a flexible cured product is required, methyldimethoxysilyl or methyldiethoxysilyl is preferred.
[0088] Crosslinked silicon groups can be used alone or in combination of two or more. Crosslinked silicon groups can exist in the main chain, side chain, or both.
[0089] As a polymerization method for (meth)acrylic acid polymers containing crosslinked silicon groups, free radical polymerization can be used. For example, conventional solution polymerization or bulk polymerization using thermal polymerization initiators such as benzoyl peroxide and azobisisobutyronitrile can be used. Alternatively, polymerization can be carried out by using a photopolymerization initiator and irradiating with light or radiation. In free radical copolymerization, chain transfer agents such as lauryl thiol or 3-mercaptopropyltrimethoxysilane can be used to adjust the molecular weight. Furthermore, free radical polymerization using thermal polymerization initiators can be used, by which polymers containing crosslinked silicon groups according to the present invention can be easily obtained. Other polymerization methods, such as the living radical polymerization method described in Japanese Patent Application Publication No. 2000-086998, can also be used.
[0090] As a moisture-curing adhesive that is solid at room temperature (A), from the perspective of not easily thickening when heated during the formation of balanced weight, the polymer containing crosslinked silicone groups (a2) is better than the urethane prepolymer containing isocyanate groups (a1).
[0091] (Silane-based adhesives) The moisture-curing adhesive (A) that is solid at room temperature according to the present invention may further contain a silane-based adhesive enhancer. The silane-based adhesive enhancer exhibits an adhesive enhancer effect through moisture curing, which can improve the adhesion to the rotating body after moisture curing, and can also improve water-resistant adhesion and heat-resistant adhesion.
[0092] From the perspective of hydrolysis rate, the crosslinking silane group of the silane adhesive is preferably an alkoxysilane group with 1 to 6 carbon atoms, such as methoxy or ethoxy. The alkoxysilane group preferably has 2 or more alkoxy groups, more preferably 3. Furthermore, the silane adhesive may also have functional groups. From the perspective of adhesiveness, the functional groups are preferably amino or epoxy groups, more preferably amino.
[0093] As a silane-based adhesive imparting agent, examples include one or more selected from the following: 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(β-aminoethyl)-3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-3-aminopropyltriethoxysilane, N-(β-aminoethyl)-3-aminopropylmethyldiethoxysilane, bis-(trimethoxysilylpropyl)amine, bis-(triethoxysilylpropyl)amine, bis-(triethoxysilylpropyl)ethylenediamine, N-[2-(vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane, and aminoethyl-aminopropyltrimethoxysilane, etc.; ketimine silanes such as N-(1,3-dimethylbutenyl)-3-(triethoxysilyl)-1-propylamine; 3-glycidyl Epoxysilanes such as glyceryloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-glycidyloxypropylmethyldiethoxysilane; (meth)acrylate silanes such as 3-methacryloyloxypropyltrimethoxysilane; vinyltrimethoxysilane, methylvinyldimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, and allyltri(β-methoxysilane); mercaptosilanes such as 3-mercaptopropyltrimethoxysilane; ureasilanes such as 3-ureapropyltrimethoxysilane and 3-ureapropyltriethoxysilane; isocyanurate silanes such as tri-(trimethoxysilylpropyl)isocyanurate; and isocyanate silanes such as 3-isocyanatopropyltriethoxysilane.
[0094] In addition, as a silane-based adhesive agent, one or more of the following can be used: the reaction product of the above-mentioned aminosilane and epoxysilane, the reaction product of aminosilane and isocyanate silane, the reaction product of aminosilane and silane having (meth)acryloyloxy group, the reaction product of aminosilane and epoxy resin (bisphenol A diglycidyl ether, phenyl glycidyl ether, etc.), the reaction product of aminosilane and polyisocyanate, the reaction product of aminosilane and polyacrylate, the condensate obtained by partially condensing the above-mentioned silanes (preferably the aminosilane condensate obtained by partially condensing the above-mentioned aminosilane, isocyanate silane, aminosilane reaction product and the mixture of the reaction product), the derivative obtained by modifying these substances, amino-modified silyl polymer, amino polymer containing crosslinked silicon group, unsaturated aminosilane complex, phenylamino long-chain alkyl silane, aminosilicone containing crosslinked silicon group, polyester containing crosslinked silicon group, photo-induced aminosilane generator, etc.
[0095] The molecular weight of silane-based adhesive binders is not particularly limited. For example, a molecular weight of 320 or more, preferably 400 or more, and more preferably 450 or more, is preferred because it is less volatile when a moisture-curing adhesive that is solid at room temperature is melted. From the perspective of adhesiveness and low volatility when hot-melt adhesives are melted, silane-based adhesive binders having two or more silane groups, such as bis-silylaminosilanes, isocyanurate silanes, aminosilane reactants, and aminosilane condensates, are preferred, with aminosilane reactants and aminosilane condensates being more preferred, and aminosilane reactants being the most preferred. In addition, aminosilane reactants can also be added separately as reactants during the mixing process and reacted.
[0096] Silane-based adhesive additives can be used alone or in combination of two or more. The amount of silane-based adhesive additive used, relative to 100 parts by weight of the isocyanate-containing urethane prepolymer or the crosslinked silicone-containing polymer, is preferably 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, particularly preferably 1 part by weight or more, preferably 20 parts by weight or less, more preferably 10 parts by weight or less, and particularly preferably 5 parts by weight or less. If it is less than 0.01 parts by weight, the effect as an adhesive additive or curing catalyst is insufficient; on the other hand, if it exceeds 20 parts by weight, the catalyst effect corresponding to the amount added is not significant, thus it is not economically preferable.
[0097] (Cross-linking catalyst) The moisture-curing adhesive (A) that is solid at room temperature according to the present invention may also contain a crosslinking catalyst. As a crosslinking catalyst, a crosslinking catalyst (silanol catalyst) of a polymer containing a crosslinkable silicon group is particularly suitable. Examples include one or more selected from titanates, tetravalent organotin compounds, divalent organotin compounds such as tin octoate, zirconium compounds, aluminum compounds, bismuth compounds, primary and secondary amines, benzyl dimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, dimorpholino diethyl ether, N,N-dimethyldodecylamine, tertiary amines such as bis-(N,N'-dimethylaminoethyl) ether, photopotential amine compounds (photoalkali generators), amidine compounds such as 1,3-diazabicyclo(5,4,6)undecene-7 or their carboxylates, fluorinated polymers, etc.
[0098] Examples of fluorinated polymers include organic polymers having Si-F bonds, such as the organic polymers with fluorosilyl groups described in International Publication No. 2015 / 088021. Among fluorinated polymers, polymers having fluorosilyl groups such as difluoromethylsilyl, difluoromethoxysilyl, difluoroethoxysilyl, or trifluorosilyl at the ends of the main chain or side chains are preferred.
[0099] As the backbone of the fluorinated polymer, polymers described in the section on liquid polymers described later can be used. Among these polymers, polyoxyalkylene polymers and / or (meth)acrylate polymers are preferred because they are easy to handle and have excellent effects in extending the bonding time. The number average molecular weight of the fluorinated polymer, as a polystyrene equivalent determined by GPC (gel permeation chromatography), is preferably 3,000 or more, more preferably 100,000 or less, more preferably 50,000 or less, and particularly preferably 30,000 or less.
[0100] When the moisture-curing adhesive (A) that is solid at room temperature according to the present invention contains a crosslinking catalyst, the content of the crosslinking catalyst is, for example, 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, for example, 10 parts by mass or less, preferably 7 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the polymer containing crosslinkable silicon groups.
[0101] (Modified resin) The moisture-curing adhesive (A) that is solid at room temperature according to the present invention may contain modified resins for adjusting curing time, reducing melt viscosity, improving or adjusting various physical properties.
[0102] Furthermore, modified resins function differently depending on the type of chain segments that constitute the target resin. Specifically, when added to resins primarily composed of hard segments, modified resins function as property modifiers; when added to resins primarily composed of soft segments, they function as tackifying resins. In particular, since the backbone of polymers containing crosslinked silicone groups is primarily composed of hard segments, the resins illustrated below function as modified resins.
[0103] Examples of modified resins include, for example, one or more selected from terpene resins, aromatic modified terpene resins, hydrogenated terpene resins, terpene-phenolic resins formed by copolymerizing terpenes and phenols, phenolic resins, modified phenolic resins, xylene-phenolic resins, cyclopentadiene-phenolic resins, coumarone-indene resins, rosin resins, rosin ester resins, hydrogenated rosin ester resins, xylene resins, low molecular weight polystyrene resins, styrene copolymer resins, styrene block copolymers, hydrogenated styrene block copolymers, petroleum resins (e.g., C5 hydrocarbon resins, C9 hydrocarbon resins, C5C9 hydrocarbon copolymer resins, etc.), hydrogenated petroleum resins, and DCPD resins.
[0104] In this invention, styrene-based block copolymers and their hydrides are preferred. Examples of styrene-based block copolymers and their hydrides include, for example, one or more selected from styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene-butene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), and styrene-isobutylene-styrene block copolymers (SIBS).
[0105] As the modified resin, terpene phenolic resins or aromatic petroleum resins are preferred from the perspectives of good compatibility with polymers containing crosslinked silicone groups and good thermal stability of the adhesive. Among the aromatic petroleum resins, aromatic styrene resins and aliphatic-aromatic copolymer styrene resins are preferred, with terpene phenolic resins and aliphatic-aromatic copolymer styrene resins being more preferred. Furthermore, from the perspectives of VOCs and fogging, aliphatic-aromatic copolymer styrene resins are preferred.
[0106] (Liquid polymer compound) The moisture-curing adhesive (A) that is solid at room temperature according to the present invention may also include a liquid polymer compound for adjusting the viscosity during melting and the curing time. The viscosity of the liquid polymer compound at room temperature (23°C) (using a type B viscometer) is 200 Pa. Below s, preferably 150 Pa less than s, more preferably 100 Pa Below s.
[0107] Examples of main chain backbones for liquid polymers include: polyoxyalkylene polymers such as polyoxypropylene, polyoxytetramethylene, and polyoxyethylene-polyoxypropylene copolymers; hydrocarbon polymers such as ethylene-propylene polymers, polyisobutylene, polyisoprene, polybutadiene, and hydrogenated polyolefin polymers obtained by hydrogenating these polyolefin polymers; polyester polymers obtained by the condensation of dicarboxylic acids such as adipic acid with glycols or by the ring-opening polymerization of lactones; (meth)acrylate polymers obtained by the free radical polymerization of monomers such as ethyl (meth)acrylate and butyl (meth)acrylate; vinyl polymers obtained by the free radical polymerization of monomers such as (meth)acrylate, vinyl acetate, acrylonitrile, and styrene; graft polymers obtained by the polymerization of vinyl monomers from organic polymers; polysulfide polymers; polyamide polymers; polycarbonate polymers; diallyl phthalate polymers, etc. These backbones can also contain two or more types in a block or random manner. Among these polymers, polyoxyalkylene polymers and / or (meth)acrylate polymers are preferred from the perspective of ease of handling.
[0108] From the perspective of imparting heat resistance through moisture curing after coating and balancing weight, liquid polymer compounds may also contain isocyanate-containing urethane prepolymers or moisture-curing functional groups of polymers containing crosslinked silicone groups.
[0109] In polymers containing crosslinked silicon groups, the crosslinked silicon groups can be bonded to the main chain, side chains, or both. From the perspective of the excellent physical properties of the cured product, such as tensile properties, the crosslinked silicon groups are preferably located at the ends of the molecular chains.
[0110] The polymer containing crosslinked silicone is mixed to adjust the curing time of a moisture-curing adhesive (A) that is solid at room temperature or to reduce its melt viscosity, and it has the function of changing and / or adjusting physical properties.
[0111] (Other ingredients) The moisture-curing adhesive (A) of the present invention, which is solid at room temperature, may also contain fillers, diluents, stabilizers, and other "other components".
[0112] {filler} Examples of fillers include inorganic fillers such as calcium carbonate, magnesium carbonate, titanium dioxide, carbon black, fused silica, precipitated silica, diatomaceous earth, kaolin, clay, talc, wood flour, walnut shell powder, rice husk powder, anhydrous silica, quartz powder, aluminum powder, zinc powder, iron powder, asbestos, glass fiber, carbon fiber, glass microspheres, aluminum hydroxide, alumina, hollow glass microspheres, volcanic ash hollow microspheres, silica hollow microspheres, calcium oxide, magnesium oxide, and silica; or wood-based fillers such as pulp and cotton scraps; powdered rubber, recycled rubber, and micro-powders of thermoplastic or thermosetting resins; and hollow polyethylene, etc. One type of filler can be added, or multiple fillers can be added in combination.
[0113] {Diluent} By adding a diluent, the viscosity and other physical properties during melting can be adjusted. Regarding the diluent, since the adhesive's operating temperature (coating, melting) is high, considering safety (fire, health) factors, a solvent (diluent) with a boiling point of 150°C or higher is preferred. The boiling point of the diluent is preferably 150°C or higher, more preferably 200°C or higher, and even more preferably 300°C or higher.
[0114] In this invention, diluents with a boiling point below 120°C may not be used, preferably diluents with a boiling point below 150°C, and more preferably diluents with a boiling point below 200°C.
[0115] Examples of diluents include phthalate esters such as dioctyl phthalate and diisodecyl phthalate; aliphatic dicarboxylic acid esters such as dimethyl adipate and dioctyl adipate; polyethers such as polypropylene glycol or its derivatives; vinyl polymers obtained by polymerizing vinyl monomers through various methods; paraffinic processing oils; naphthenic oils; synthetic waxes such as Fischer-Tropsch wax, polyethylene wax, polypropylene wax, and atactic polypropylene; and petroleum waxes such as paraffin wax and microcrystalline wax. These diluents can be used alone or in combination of two or more.
[0116] {Stabilizer} As a stabilizer, one or more can be selected from antioxidants, light stabilizers, ultraviolet absorbers, etc.
[0117] When antioxidants are included, the weather resistance and heat resistance of the cured composition for balancing weights can be improved. Examples of antioxidants include one or more selected from hindered phenolic antioxidants, monophenolic antioxidants, bisphenolic antioxidants, and polyphenolic antioxidants. Hindered phenolic antioxidants are particularly preferred.
[0118] When a light stabilizer is included, photo-oxidative degradation of the cured product of the composition used for balancing weights can be prevented. Examples of light stabilizers include one or more selected from benzotriazole light stabilizers, hindered amine light stabilizers, and benzoate light stabilizers. Hindered amine light stabilizers are particularly preferred.
[0119] When a light stabilizer is included, the surface weather resistance of the cured composition for balancing weights can be improved. As a UV absorber, one or more can be selected from, for example, benzophenone-based light stabilizers, benzotriazole-based light stabilizers, salicylate-based light stabilizers, substituted toluene-based light stabilizers, and metal chelate compounds. Benzotriazole-based light stabilizers are particularly preferred.
[0120] As stabilizers, phenolic antioxidants, hindered phenolic antioxidants, hindered amine light stabilizers, and benzotriazole ultraviolet absorbers are preferred, for example, in combination.
[0121] <Tungsten Powder (B)> As for tungsten powder (B), there are no particular limitations as long as the powder is mainly composed of tungsten. For example, one or more types selected from tungsten powder, tungsten alloy powder, and tungsten compound powder can be used.
[0122] As a tungsten alloy powder, for example, one or more tungsten alloy powders that are mainly composed of tungsten and include one or more tungsten alloy powders selected from iron, copper, nickel, etc. can be listed.
[0123] As a tungsten compound powder, one or more of the following can be selected, for example, from tungsten carbide, tungsten oxide, ceramics with tungsten as the main component.
[0124] In this invention, the particle size of the tungsten powder (B) is not particularly limited. For example, it is 0.1 μm or more, preferably 1.0 μm or more, more preferably 2.0 μm or more, for example, 100.0 μm or less, preferably 80.0 μm or less, more preferably 60.0 μm or less.
[0125] When the particle size of tungsten powder (B) is less than 0.05 μm, the viscosity of the balancing composition tends to increase when heated and melted, which may reduce workability. When the particle size of tungsten powder (B) exceeds 100 μm, there is a risk that tungsten powder (B) may precipitate when the balancing composition is heated and melted.
[0126] In this invention, tungsten particles (B) with different particle sizes can be combined in a range of 0.1 to 100 μm.
[0127] In this invention, the specific gravity of the tungsten powder is not particularly limited. For example, it is 10.0 or more, preferably 11.0 or more, more preferably 13.0 or more, for example, 20.5 or less, preferably 20.0 or less, more preferably a specific gravity of tungsten of 19.30 or less.
[0128] Commercially available tungsten powders include, for example, those manufactured by Nippon Shin-Gold Industries, such as "W-H" (particle size: 0.45~0.59μm) and "W-6" (particle size: 8.0~16.0μm), and those manufactured by Allied Material, such as "A20" (particle size: 0.5~0.6μm) and "W-U250" (particle size: 23~28μm). In this invention, one or more of these powders may be used.
[0129] Commercially available tungsten powders, including tungsten carbide powder, include tungsten compound powders such as "WC-10" (particle size: 0.70~1.19μm) and "WC-90" (particle size: 7.5~12.0μm) manufactured by Nippon Shin-Gold Industries, Ltd., and "WC08" (particle size: 0.7~0.9μm) and "WC60" (particle size: 5.0~7.1μm) manufactured by Allied Material Co., Ltd. In this invention, one or more of these powders may be used.
[0130] <Preparation Method of Composition for Balancing Weights> In the balancing weights involved in this invention, for example, the balancing weights can be adjusted by mixing tungsten (B) during the manufacture of a moisture-curing adhesive (A) that is solid at room temperature.
[0131] The preparation method of the reactive hot melt adhesive involved in this invention is not particularly limited. For example, conventional methods can be used, such as mixing the above-mentioned components in a specified ratio and mixing them at room temperature or under heating using a mixer, roller, kneader, etc., or dissolving and mixing the components using a small amount of specified solvent.
[0132] The viscosity of the balancing weight involved in this invention is preferably 200 Pa at 120°C. Below s, more preferably 180 Pa Below s, 160 Pa is further preferred. Below s. If the viscosity at 120℃ exceeds 200 Pa. If the temperature is too low, the material output or workability will decrease, or higher temperatures may be required to ensure the material output or workability. In such cases, it becomes difficult to use on substrates with low heat resistance, thus limiting the range of applications.
[0133] [Balance Weight] The specific gravity of the counterweight involved in this invention is 8.5 or less. The lower limit of the specific gravity of the counterweight is, for example, 2.0 or more, preferably 3.0 or more, and more preferably 4.0 or more. From the perspective of output quality, workability, etc., the upper limit of the specific gravity of the counterweight is 8.5 or less, preferably 8.3 or less, more preferably 8.2 or less, and even more preferably 8.0 or less.
[0134] The balancing weight of the present invention is suitable for attachment to a rotating body, such as the impeller of a fan motor, especially the rotor of a brushless motor, for adjusting balance.
[0135] For example, it can be used as a counterweight for the impeller (rotor) of a brushless motor, i.e., a fan motor, which is rotatably supported by a bearing mounted in the center of the fan motor body via a shaft.
[0136] Impellers can become unbalanced due to uneven mass distribution centered on the shaft caused by assembly deviations, component dimensional deviations, manufacturing deviations, etc. In such cases, the imbalance can be eliminated by applying the balancing weight of this invention.
[0137] The balancing weight involved in this invention is obtained by curing a composition containing a moisture-curing adhesive (A) that is solid at room temperature and tungsten particles.
[0138] The balancing weight is adjusted to achieve a specific gravity of 4.0 or higher after moisture curing, making it suitable as a material for adjusting imbalances in rotating bodies. Since the balancing weight composition cures instantly after coating, the overall equilibrium state can be measured. Furthermore, the cross-linking reaction is initiated by moisture in the air, thereby significantly improving adhesion to the rotating body.
[0139] In this invention, for the tungsten particles (B), it is preferable to use tungsten particles (B) with a specific gravity of 10.0 or more and a particle size in the range of 0.1 to 100 μm.
[0140] The balancing weight of the present invention is based on the fact that the moisture-curing adhesive (A) is solid at room temperature. Therefore, after being heated, melted and applied to the rotating body, the adhesive immediately cools to below the softening point or melting point and solidifies. Thus, the overall equilibrium state of the rotating body can be determined.
[0141] In the balancing weights of this invention, it is important that the moisture-curing adhesive (A), which is solid at room temperature, has a low viscosity when heated to melt. For example, the viscosity at 120°C is preferably 100 Pa. Below s, more preferably 50 Pa Below s, 40 Pa is further preferred. Below s.
[0142] <Construction method using a balanced counterweight for moisture-curing adhesives that are solid at room temperature> The construction method for the counterweight according to the present invention can be the same as that for various known reactive hot melt adhesives. For example, the construction method includes a step of heating the counterweight according to the present invention to a temperature in the range of 50°C to 130°C (heating step), and a step of applying the heated counterweight to the balance adjustment area of the rotating body (coating step).
[0143] The present invention relates to a balancing weight using a moisture-curing adhesive that is solid at room temperature. Because it comprises a moisture-curing adhesive that is solid at room temperature and mainly consists of a urethane prepolymer containing isocyanate groups or a polymer containing cross-linked silicone groups, the balancing weight cures immediately after application, preventing sagging or shifting when applied to a rotating body. Furthermore, due to the use of a moisture-curing adhesive, the cured product after moisture curing acquires adhesive properties or heat resistance.
[0144] Example The following examples provide a more detailed description. These examples are illustrative and not intended to be limiting. Unless otherwise specified, "parts" in these examples refers to parts by mass, and "%" refers to "% by mass".
[0145] [Synthesis example 1] 70 parts of methyl methacrylate, 30 parts of 2-ethylhexyl methacrylate, 8 parts of 3-methacryloyloxypropyltrimethoxysilane, 0.1 parts of titanium dichlorodecane as a metal catalyst, and 40 parts of ethyl acetate as an organic solvent were added to a reaction vessel and heated to 80°C under a nitrogen atmosphere with stirring. Then, 3.4 parts of mercaptoethanol were added, and the reaction was carried out for 16 hours while maintaining the temperature of the reaction vessel at 80°C through heating and / or cooling. After 16 hours of reaction, the temperature of the reactants was returned to room temperature (23°C) to terminate the polymerization, yielding a solution of a hydroxyl-containing crosslinked silicone polymer (a1) (66% by mass of non-volatile components).
[0146] The number-average molecular weight of the hydroxyl-containing crosslinked silicone (meth)acrylic polymer (a1), determined by gel permeation chromatography (GPC), was 4,755.
[0147] [Synthesis example 2] 100 parts of polypropylene glycol ethylene oxide adduct (manufactured by Mitsui Chemicals SKC, "EDL-S101" (number average molecular weight 7,000)), 84.7 parts of adipic acid / 1,6-hexanediol crystalline aliphatic polyester polyol (manufactured by Toyokuni Oil Company, "HS2H-201AP" (number average molecular weight 2,000)), and 31.9 parts of adipic acid / 1,6-hexanediol crystalline aliphatic polyester polyol (manufactured by Toyokuni Oil Company, "HS2H-451A" (number average molecular weight 4,500)) were melt-mixed at 100°C for 1 hour, followed by dehydration under reduced pressure to obtain a polyol mixture. 23.9 parts of diphenylmethane diisocyanate (MDI) (manufactured by Tosoh Corporation, "MILLIONATE MT") were added to the obtained polyol mixture, and the mixture was reacted at 100°C for 3 hours under a nitrogen atmosphere with stirring to obtain a urethane prepolymer (a2).
[0148] Add 64.7 parts (solid content conversion) of the crosslinked silicone-containing (meth)acrylic polymer (a1) obtained in Synthesis Example 1 and 13.3 parts of N-phenyl-3-aminopropyltrimethoxysilane (a3) (manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBMB573" (phenylaminosilane)) to the obtained urethane prepolymer (a2), stir at 100°C for 2 hours, and react until the -NCO absorption from the isocyanate group disappears in the IR spectrum measurement.
[0149] After the reaction was completed, the solvent was distilled off to obtain a polymer containing crosslinked silicon groups (polymer A).
[0150] [Synthesis example 3] To a flask equipped with a stirrer, nitrogen inlet tube, thermometer, and reflux condenser, add 70 parts of methyl methacrylate, 30 parts of 2-ethylhexyl methacrylate, 12 parts of γ-methacryloyloxypropyltrimethoxysilane, 0.1 parts of titanium dichlorodecane as a metal catalyst, and 40 parts of ethyl acetate as an organic solvent. While introducing nitrogen into the flask, heat the contents to 80°C and stir. Then, add 8.5 parts of 3-mercaptopropyltrimethoxysilane, which has been fully purged with nitrogen, to the stirred flask in one go. Continue stirring while heating and cooling, maintaining the temperature at 80°C for 16 hours. After the reaction, return the reactants to room temperature (23°C) to complete the polymerization, yielding an ethyl acetate solution of a crosslinked silyl-containing (meth)acrylic polymer (polymer B) with two silyl groups per molecule.
[0151] The monomer residue of polymer B in ethyl acetate solution was determined by gas chromatography (GC), and the polymerization rate was calculated to be 97%.
[0152] Regarding the ethyl acetate solution of polymer B, the viscosity at 25°C is 2.2 (Pa). (s), heated to 105℃ and the solid content was calculated, the result was 70.5%.
[0153] Furthermore, the molecular weight of polymer B was determined by gel permeation chromatography (GPC) to be 3800 (weight average molecular weight), 1500 (number average molecular weight), and 2.4 (polydispersity index).
[0154] [Synthesis Example 4] 25 parts of polypropylene glycol (manufactured by AGC, "EXCENOL2020" (hydroxyl number 2, Mn 2000), 25 parts of adipic acid / 1,6-hexanediol crystalline aliphatic polyester polyol (manufactured by Toyokuni Oil Company, "HS2H-451A" (number average molecular weight 4,500)), and 50 parts of aromatic amorphous polyester polyol (manufactured by Toyokuni Oil Company, number average molecular weight 2,000) were melt-mixed at 100°C for 1 hour, and then dehydrated under reduced pressure to obtain a polyol mixture. 21.0 parts of diphenylmethane diisocyanate (MDI) (manufactured by Tosoh Corporation, "MILLIONATE MT") were added to the obtained polyol mixture, and the mixture was reacted at 100°C for 3 hours under a nitrogen atmosphere with stirring to obtain a urethane prepolymer (polymer C).
[0155] [Determination Method] In Synthetic Examples 1, 2, and 3, the number-average molecular weight and IR spectra were determined in the following manner.
[0156] <Number Average Molecular Weight> Under the following determination conditions, the analytes were determined by gel permeation chromatography (GPC), with polystyrene as the standard substance, and the highest frequency molecular weight obtained by converting to standard polyethylene glycol was taken as the number average molecular weight.
[0157] Measuring apparatus: Gel permeation chromatography analyzer (manufactured by Tosoh Corporation, "HLC-8220") Chromatographic columns used: 1 G7000HXL (manufactured by Tosoh Corporation), 2 GMHXL (manufactured by Tosoh Corporation), and 1 G2000HXL (manufactured by Tosoh Corporation). Solvent: Tetrahydrofuran Flow rate: 1.0 ml / min Measurement temperature: 40℃ <IR Spectroscopy> Measurement Apparatus: FT-IR measurement apparatus (manufactured by Japan Spectrophotometer Co., Ltd., "FT-IR460Plus") [Manufacturing Example 1] The polymer A obtained from Synthesis Example 2, the polymer B obtained from Synthesis Example 3, resin A, resin B, moisture absorbent, silane adhesive additive, and crosslinking catalyst were mixed according to the mixing ratio (solid content; parts by mass) shown in Table 1, and stirred at 120°C. Finally, degassing under reduced pressure was performed to produce a moisture-curing adhesive A-1 that is solid at room temperature (23°C).
[0158] [Manufacturing Examples 2, 3, 4, 5] The components shown in Table 1 were mixed according to the mixing ratio (solid content; parts by mass) shown in Table 1. Otherwise, moisture-curing adhesives A-2, A-3, A-4, A-5 and A-6, which are solid at room temperature (23°C), and adhesive A'-1, which is liquid at room temperature (23°C), were manufactured in the same manner as in Manufacturing Example 1.
[0159] [Table 1]
[0160] The components shown in Table 1 are as follows.
[0161] Polymer A: The cross-linked silicon-containing polymer obtained from Synthesis Example 2 Polymer B: A crosslinked silyl-containing (meth)acrylic polymer with two silyl groups per molecule, obtained from Synthesis Example 3. Polymer C: The urethane prepolymer obtained from Synthesis Example 4 Resin A: Styrene resin (manufactured by YASUHARA CHEMICAL, "YS RESIN SX100") Resin B: Modified silicone resin (manufactured by KANEKA, "SAX220") Moisture absorbent: Vinyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM1003") Adhesion enhancer: N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM603") Crosslinking catalyst: Dioctyltin compounds (manufactured by Nitto Kasei Corporation, "Neostann U-830") Adhesive A: Moisture-curing adhesive (manufactured by CEMEDINE, "Super XG No. 777") Viscosities at 120℃ (Pa) in Table 1 s) is determined by the following method.
[0162] Moisture-curing adhesives A-1, A-2, A-3, A-4, A-5, and A-6, which are solid at room temperature (23℃), were heated to 120℃ to melt them, and their viscosities were measured using a cone-plate viscometer CV-1 (manufactured by Toa Industrial Co., Ltd., cone diameter: 14.5 mm, cone angle: 2.0°, rotation speed: 20 rpm).
[0163] In addition, since the adhesive A used in manufacturing example 7 in Table 1 is a liquid at room temperature (23°C), the viscosity at 120°C is not measured, and the viscosity at room temperature (23°C) is recorded in Table 1.
[0164] [Example 1] 100 parts of moisture-curing adhesive A-1 obtained in Manufacturing Example 1 as moisture-curing adhesive (A) and 250 parts of tungsten powder B as tungsten powder (B) were mixed, stirred at 120°C and degassed under reduced pressure to prepare a composition for balancing weight.
[0165] [Examples 2-18, Comparative Example 1] The substances shown in Tables 2 to 4 were used as moisture-curing adhesive (A) and tungsten powder (B), respectively. Otherwise, the composition for balancing weight was prepared in the same manner as in Example 1.
[0166] [Comparative Example 2] Moisture-curing adhesive A'-1, which is liquid at room temperature (23°C), was used as moisture-curing adhesive (A). Otherwise, the composition for balancing weight was prepared in the same manner as in Example 1.
[0167] The components used in Examples 2-17 and Comparative Examples 1 and 2 are shown below.
[0168] Moisture-curing adhesive A-1: The moisture-curing adhesive A-1 shown in Table 1 is solid at room temperature (23℃). Moisture-curing adhesive A-2: As shown in Table 1, moisture-curing adhesive A-2 is solid at room temperature (23℃). Moisture-curing adhesive A-3: As shown in Table 1, moisture-curing adhesive A-3 is solid at room temperature (23℃). Moisture-curing adhesive A-4: As shown in Table 1, moisture-curing adhesive A-4 is solid at room temperature (23℃). Moisture-curing adhesive A-5: As shown in Table 1, moisture-curing adhesive A-5 is solid at room temperature (23℃). Moisture-curing adhesive A-6: As shown in Table 1, moisture-curing adhesive A-6 is solid at room temperature (23℃). Moisture-curing adhesive A'-1: A moisture-curing adhesive that is liquid at room temperature (23°C) (manufactured by CEMEDINE, trade name "Super XG No. 777"). (Viscosity: 85.0 Pa) s / 23℃) Tungsten Powder A: Tungsten powder (manufactured by Shin-Metal Corporation, Japan, trade name "W-6" (particle size 8.0~16.0μm; specific gravity 19.3)) Tungsten Powder B: Tungsten powder (manufactured by Shin-Metal Corporation, Japan, trade name "WL" (particle size 10.0~40.0μm; specific gravity 19.3)) Tungsten powder C: Tungsten powder (manufactured by Allied Material, trade name "D100" (particle size 7.6~12.0μm; specific gravity 19.3)) Tungsten powder D: Tungsten powder (manufactured by Allied Material, trade name "Coarse" (particle size 23.0~28.0μm; specific gravity 19.3)) Tungsten powder E: Tungsten powder (manufactured by Allied Material, trade name "W-U250" (particle size 23.0~28.0μm; specific gravity 19.3)) [Physical properties, tests] Specific gravity The balancing composition obtained in Example 1 was melted at 120°C, coated onto a peelable surface, and cured to produce a sheet measuring 1cm × 1cm × 1mm. After curing the sheet at 23°C and 50% RH for one week, its specific gravity was determined using the water displacement method according to Japanese Industrial Standard JIS K 7112. The results are shown in Table 2.
[0169] Similarly, sheets were prepared using the balancing compositions obtained in Examples 2-18 and Comparative Examples 1 and 2, and their specific gravities were measured. The results are combined and shown in Tables 2-4.
[0170] <Shear bond strength after 5 minutes> The balancing composition obtained in Example 1 was melted at 120°C and then coated onto a first aluminum plate (25mm × 75mm × 2mm) whose coated surface had been degreased with acetone, achieving a thickness of 100μm. Immediately after coating, a second aluminum plate (25mm × 75mm × 2mm) whose adhesive surface had also been degreased with acetone was bonded to the coated surface with an overlap of 25mm × 2mm starting from one end to create a test specimen. After curing the test specimen at 23°C and 50%RH for 5 minutes, the shear bond strength (initial shear bond strength after 5 minutes) (N / mm²) was measured at a tensile speed of 50mm / min according to Japanese Industrial Standard JIS K 6850. The results are combined and shown in Table 2.
[0171] Similarly, test specimens were prepared using the balancing weight compositions obtained in Examples 2-18 and Comparative Examples 1 and 2, and the shear bond strength (N / mm²) of each test specimen was measured after 5 minutes. 2 The results are shown in Tables 2 through 4.
[0172] <Extrudability> Extrusion tests were conducted using an air pulse dispensing machine "ML-808FX" manufactured by Musashi Engineering Co., Ltd., a benchtop coating robot "SHOTMASTER 300DS" manufactured by Musashi Engineering Co., Ltd., and a metal needle "SNA19G-B" manufactured by Musashi Engineering Co., Ltd. The coating conditions were set at a coating pressure of 200 kPa and a coating time of 10 seconds, and the extrusion volume under these conditions was measured.
[0173] [evaluate] The balancing compositions of Examples 1-18 and Comparative Examples 1 and 2 were evaluated in the following manner.
[0174] <Automation Characteristics> In the extrusion test, a value of 15 mg / 10 seconds or higher is rated A (pass), and a value of less than 15 mg / 10 seconds is rated D (fail). The evaluation results are combined and shown in Tables 2 to 5.
[0175] <Suppression of sagging and offset characteristics> In the shear bond strength test after 5 minutes, a value above 0.2 MPa is rated A (pass), and a value below 0.2 MPa is rated D (fail). The evaluation results are combined and shown in Tables 2 to 5.
[0176] [Table 2]
[0177] [Table 3]
[0178] [Table 4]
[0179] Tables 2-4 confirm that the balancing composition described in the examples exhibits good extrudability and demonstrates excellent automation characteristics in automating the coating of the balancing composition. Therefore, by automatically coating the balancing composition, the equilibrium state can be easily adjusted through the dynamic balancing of the rotating body, thereby improving workability.
[0180] As confirmed by Tables 2-4, the balancing composition involved in the examples exhibits good automation characteristics, and the coating of the balancing composition demonstrates excellent automation characteristics. Therefore, when automatically coating the balancing composition, an appropriate amount can be precisely applied, and the equilibrium state can be easily adjusted through the dynamic balancing of the rotating body, thereby improving workability.
[0181] As confirmed by Tables 2-4, the balancing weight composition involved in the examples exhibits good shear bond strength after 5 minutes (initial shear bond strength after 5 minutes), fast curing speed (excellent fast curing and fast bonding), and excellent anti-sagging and anti-deviation properties. Therefore, even if the equilibrium state is measured immediately after coating, sagging or deviation of the balancing weight composition can be suppressed, allowing the process to proceed to the next step and improving workability.
[0182] On the other hand, as shown in Tables 2-4, although the balancing composition with a specific gravity of 9.0 in Comparative Example 1 exhibits excellent shear bond strength after 5 minutes, it also has poor extrudability and unsatisfactory automation characteristics. Furthermore, the balancing composition in Comparative Example 2, which uses a moisture-curing adhesive that is liquid at room temperature (23°C), has high viscosity at 23°C. Heating would cause moisture curing, leading to difficulties in coating. Therefore, it was confirmed that coating at 23°C resulted in lower shear bond strength, extrudability, and automation characteristics after 5 minutes, and poorer fast curing, fast bonding, automation characteristics, and anti-sagging and anti-deviation characteristics. Thus, it can be concluded that for balancing compositions using moisture-curing adhesives that are liquid at room temperature (23°C), it is difficult to immediately determine the equilibrium state after coating, and the likelihood of sagging or deviation of the coated balancing weight increases before proceeding to the next process.
Claims
1. A composition for balancing counterweights, characterized in that, Include: Moisture-curing adhesive that is solid at room temperature (A); Tungsten powder (B) The composition for balancing counterweights is a solid at room temperature and has a specific gravity of 8.5 or less.
2. The composition for balancing counterweights according to claim 1, characterized in that, The moisture-curing adhesive (A), which is solid at room temperature, has urethane prepolymers containing isocyanate groups or polymers containing cross-linked silicone groups as its main components.
3. The composition for balancing counterweights according to claim 1, characterized in that, The moisture-curing adhesive (A), which is solid at room temperature, has a viscosity of 50 Pa at 120°C. Below s, The particle size of the tungsten powder (B) is in the range of 0.1~200μm.
4. A counterweight, characterized in that, It involves applying the balancing composition according to any one of claims 1 to 3 to the desired part of the rotating body to adjust the balance of the rotating body.
5. A method, characterized in that, It is a method of applying the balancing composition of any one of claims 1 to 3 to the application site of a rotating body to adjust the balance.
Citation Information
Patent Citations
Counter
JP1977022467A
Balancing material for rotary electric element
JP1991107646A
Reactive hot melt adhesive
JP2000086998A
Motor
JP2001298925A
Brushless motor
JP2001298929A
